Hydrolysis of particulate settleable solids (PSS) in activated sludge is determined by the bacteria initially adsorbed in the sewage. (15th November 2017) - Benneouala, Mourad; Bareha, Younès; Mengelle, Evrard; Bounouba, Mansour; Sperandio, Mathieu; Bessiere, Yolaine; Paul, Etienne
Abstract: Up to half of the organic fraction of an urban wastewater is made up of particulate settleable solids (PSS). In activated sludge process (AS) this material is rapidly adsorbed on to microbial flocs but is only slowly and partially degraded. To better understand and predict the degradation kinetics observed, a determination of the proportion of hydrolytic bacteria is required. As inoculum is usually added in the biodegradation tests, a comparison is required between the roles of bacteria introduced with the inoculum and those attached to the substrate. In this work, respirometric batch experiments were performed on PSS collected from upstream or downstream of the sewers of Toulouse city. Toilet paper (TP) and cellulose, two model particulate substrates, were also investigated. To understand the role of the active biomass in hydrolysis, increasing concentrations of AS were added to a certain amount of PSS or TP. No correlation was observed between the concentration of AS and the rate and duration of degradation of the particulate matter. Simulations performed after calibration of the model ASM-1 allowed the fraction of hydrolytic bacteria to be estimated in both the substrate and the AS-inoculum. Only a very small fraction of the bacteria of AS and of the substrate samples were found to be efficient for hydrolysis. Hydrolysis was mainly initiated by a small proportion of the microorganisms, and especially by cells already attached to PSSs. Moreover, the fraction of bacteria able to hydrolyse large particles present in an inoculum of AS depended on the initial contamination of the surface of the particles. Graphical abstract: Highlights: Particle hydrolysis by attached bacteria and activated sludge inoculum were compared. Only a small fraction of activated sludge inoculum contributed to hydrolysis. A high fraction of attached and inoculum cells performed only endogenous respiration. Modelling was used to evaluate the source of hydrolytic biomass. Inoculum acclimatization allows only slightly decreasing particle hydrolysis time.